2019
DOI: 10.3390/molecules24091748
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin’s Inhibition and Treatment Effects for Alzheimer’s Disease

Abstract: As a longstanding problem, Alzheimer’s disease (AD) has stymied researchers in the medical field with its increasing incidence and enormous treatment difficulty. Silymarin has always been valued by researchers for its good efficacy and safety in treating liver disease. Recent studies have shown that silymarin also has good pharmacological activity in the nervous system, especially for the treatment of AD. Silymarin can control the production of Aβ by inhibiting the precursor substance of Aβ (β-amyloid precurso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 103 publications
(123 reference statements)
0
24
0
Order By: Relevance
“…In a mouse model, it has been shown that Silymarin treatment was associated with a decline in A␤ oligomer production [94]. Silymarin can control the production of A␤ by inhibiting the precursor substance of A␤, A␤PP, and has potential for the treatment of AD [95].…”
Section: Flavonoidsmentioning
confidence: 99%
“…In a mouse model, it has been shown that Silymarin treatment was associated with a decline in A␤ oligomer production [94]. Silymarin can control the production of A␤ by inhibiting the precursor substance of A␤, A␤PP, and has potential for the treatment of AD [95].…”
Section: Flavonoidsmentioning
confidence: 99%
“…It is one of the direct causes of aging and a known cause of AD (Jiang et al, 2016). The brain has high oxygen consumption and low antioxidant capacity, which makes it particularly vulnerable to oxidative stress (Guo et al, 2019). Free radicals and ROS are the two main pathways used by oxidative stress to directly damage nerve cells.…”
Section: Myr and Dmy Exert An Anti-ad Effect Through Antioxidantmentioning
confidence: 99%
“…Acetylcholine is a neurotransmitter that plays an important role in the transmission of neural signals and memory formation and the lack of ACh in the central nervous system is a known cause of AD (Guo et al, 2019). AChE has been a major target for drug discovery in recent years with three of the current five AD clinical drugs being AChE inhibitors.…”
Section: Myr and Dmy Play An Anti-ad Role By Inhibiting Achementioning
confidence: 99%
See 2 more Smart Citations